PROTECTION OF OUTSOURCING WORKERS IN THE PERSPECTIVE OF LAW NUMBER 11 OF 2020 CONCERNING JOB CREATION - Ristyawan Aji Nugroho; Bintara Sura Priambada; S. Andi Sutrasno (Universitas Surakarta, 2022)
The purpose of this article is to find out the legal protection for outsourcing workers according to the provisions of Law Number 11 of 2020 concerning Job Creation. The type of research used is empirical legal research. Associated with the type of empirical legal research, the data used in the form of primary data and secondary data. Primary data were obtained through interviews while secondary data were obtained from primary legal materials, secondary legal materials and tertiary legal materials. The results of the study can be concluded that legal protection efforts against outsourcing workers/labor must be carried out maximally and more specifically, considering that in the practice of outsourcing there is a triangular employment relationship involving the employer (principal), the employer (vendor) and the worker/laborer. Under these conditions, outsourcing workers/laborers are very vulnerable to exploitation and inhumane acts, either because of their status as non-permanent (contracted) workers/laborers or because of the treatment of entrepreneurs who tend to act like capitalists who seek profit from their hard work. The vendor's business is to employ workers/laborers for the benefit of the principal, while the vendors themselves benefit from the difference between the wages/services provided by the principal to the vendor and the wages paid by the vendor to the workers/laborers. This practice has been analyzed by Marx, who said that workers are alienated (exiled) from work, because once the worker/laborer is in an outsourcing situation, the worker will work based on the purpose of the vendor who pays and pays wages, and they (the worker/labor) it will be exploited for the benefit of the vendor and principal. Keywords: legal protection, outsourcing workers, Job Creation Act.